Characterization of Lead–Phytochelatin Complexes by Nano-Electrospray Ionization Mass Spectrometry - Scheidegger, Christian; Suter, Marc J.; Behra, Renata; Sigg, Laura (Frontiers in Microbiology, 2012)
The role of phytochelatins (PCn, metal-binding oligopeptides with the general structure (γGlu - Cys)n - Gly (n = 2- 11)) in metal detoxification is assumed to be based on immobilization of metals, which prevents binding of metals to important biomolecules. Although induction of phytochelatin synthesis has often been observed in algae upon exposure to metals, direct evidence for binding of the inducing metal to phytochelatins is scarce. In this study, a nano-electrospray ionization mass spectrometry (nano-ESI-MS) method is developed for identification and characterization of Pb(II)-PCn and Zn(II)-PCn complexes. Complexes of Pb(II) with standard PCn (n = 2 - 4) were examined by nano-ESI-MS with respect to their stoichiometry. Pb-PCn mass spectra indicated the presence of the [M+H]+ peak of PCn and complexes with various stoichiometries. Analysis of Pb-PC2 allowed the identification of four different complexes observed at m/z 746.10, 952.06, 1285.24 and 1491.20, corresponding to [Pb-PC2]+, [Pb2-PC2]+, [Pb-(PC2)2]+ and [Pb2-(PC2)2]+. Their m/z indicated coordination of Pb(II) by PC2 through the thiol groups of PC cysteine and possibly carboxylic groups. For each of the standard PC3 and PC4, two different complexes were observed, corresponding to Pb-PC3, Pb2-PC3, Pb-PC4 and Pb2-PC4. The measured isotopic patterns were for all complexes identical to the theoretical isotopic patterns. Addition of Zn(II) to previously formed Pb-PC2 complexes showed the appearance of the [Zn-PC2]+ complexes at m/z 602.6 and the decrease of the [Pb-PC2]+ peak. These findings corroborate the postulated Pb-PC complexes from a previous study using size exclusion chromatography of PC extracted from algae, as well as the concurrent formation of Pb-, Zn- and Cu-PC complexes in algae.